Writing Hollywood: The Work and Professional Culture of Television Writers, Patricia F. Phalen (2018). (1st March 2020) - Morgasen, David
Writing Hollywood: The Work and Professional Culture of Television Writers, Patricia F. Phalen (2018)New York: Routledge, 110 pp., ISBN 978-1-13822-982-2, p/bk, $42.95